Atractyloside Protect Mice Against Liver Steatosis by Activation of Autophagy via ANT-AMPK-mTORC1 Signaling Pathway - Zhang, Pengfei; Cheng, Xinyu; Sun, Huimin; Li, Yajing; Mei, Wuxuan; Zeng, Changchun (Frontiers in Pharmacology, 2021)
Objective: Adenine nucleotide translocase (ANT) can transport ADP from cytoplasm to mitochondrial matrix and provide raw materials for ATP synthesis by oxidative phosphorylation. Dysfunction of ANT leads to limitation of ADP transport and decrease of ATP production. Atractyloside (ATR) is considered as a cytotoxic competitive inhibitor binding to ANT, making ANT vulnerable to transport ADP, and reduces ATP synthesis. Moreover, the blockage of ANT by ATR may increase ADP/ATP ratio, activate AMPK-mTORC1-autophagy signaling pathway, and promote lipid degradation in steatosis hepatocytes. The present study was conducted to investigate the mechanism of ATR, regulate ANT-AMPK-mTORC1 signaling pathway to activate autophagy, and promote the degradation of lipid droplets in high-fat diet (HFD) induced liver steatosis. Methods: ICR mice were fed with HFD for 8 weeks to induce liver steatosis, and ATR solution was given by intraperitoneal injection. Intracellular triglyceride level and oil red O staining-lipid droplets (LDs) were assessed, the expression of proteins related to ANT-AMPK-mTORC1 signaling pathway and autophagy were determined, and the colocalization of LC3B and Perilipin 2 was performed. Results: ATR treatment decreased the serum AST level, relative weight of liver and epididymal fat, and body weight of HFD mice. The LDs in HFD mice livers were reduced in the presence of ATR, and the TG level in serum and liver of HFD mice was significantly reduced by ATR. In addition, ATR inhibited ANT2 expression, promoted the activation of AMPK, then increased Raptor expression, and finally decreased the mTOR activity. Furthermore, ATR increased the protein level of LC3A/B and ATG7, and a strong colocalization of LC3B and PLIN2 was observed. Conclusion: ATR treatment blocks ANT2 expression, promotes the activation of AMPK, then decreases the mTOR activity, and finally promotes autophagosomes formation, thus accelerating the degradation of HFD-induced accumulated lipids in the liver. This will provide new therapeutic ideas and experimental data for clinical prevention and treatment of non-alcoholic fatty liver disease.